EVALUATION OF THE ADIWIYATA PROGRAM IN ESTABLISHING ENVIRONMENTALLY FRIENDLY SCHOOLS AT SDN BENCONGAN VII - Rabiatul Asiah, Mina; Nurul Anriani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
SDN Bencongan VII is a provincial-level Adiwiyata predicate school located in Tangerang Regency. This school has implemented the Adiwiyata program for approximately five years starting in 2018. Based on previous research, the implementation of the Adiwiyata program still faces many obstacles, especially in student participation. Therefore, in this research, an evaluation of the Adiwiyata Program will be carried out at SDN Bencongan VII. The method used in this research is. The subjects involved in this research were the Adiwiyata Team, school principals, teachers, education staff, and students at SDN Bencongan VII. The data collection techniques used in the research consisted of observation, interviews and questionnaires. Based on the results of the program evaluation, it is known that according to success indicators, the Adiwiyata program at SDN Bencongan VII is still not completely successful or successful. Some indicators have not been met, especially indicators related to program-supporting infrastructure.